The Challenges and Opportunities in Training Muslim Chaplaincy Students for a Burgeoning New Field - Salem, Feryal (Journal of pastoral theology, 2022)
Though a relatively new field, Islamic chaplaincy has become integral to many spiritual care and religious life divisions of public institutions that have undergone a significant shift towards a multifaith presence in approximately the last fifty years. These changes promote new opportunities in which Muslim chaplains can enrich religious life through their distinctive contributions to the field. Simultaneously, there are challenges that need to be addressed such as hiring practices that provide balanced support for Muslim chaplains, the avoidance of tokenization tendencies through ensuring the proper education of students training to become Muslim chaplains, and the need for such students to have their own space for development and formation that does not compromise their religious identities in Christian majority contexts. These challenges have facilitated creative solutions as well as calls for action from interfaith allies.